Politik Etnisitas Dalam Upaya Pemekaran Provinsi Kotawaringin - Ricky Zulfauzan; Kris Nugroho; Dwi Widyatuti Budi (JURNAL SOSIAL HUMANIORA (JSH), 2019)
This study aims to provide a descriptive analysis of ethnicity politics from the perspective of Glazer and Moynihan "Beyond The Melting Pot" to expand Kotawaringin Province. The research method used is qualitative with a case study approach. The research data were obtained from observations, document searches and in-deep interviews. The results found that the desire to separate from Central Kalimantan Province made the five prospective regencies of Kotawaringin Province form a Melting Pot. "Melting Pot," which is meant here, is to be "Orang Kotawaringin." The Kotawaringin community is very heterogeneous, originating from not only one ethnicity but being able to unite for a common goal.In contrast to Glazer and Moynihan's "Being America," which illustrates the pattern of ethnic interaction in New York City is eternal. In Kotawaringin, this ethnic identity is only temporary and impermanent. The collective identity of being an Orang Kotawaringin is built according to an instrumentalist perspective, namely: ethnicity is seen not only as a given value or as a result of a social construction but rather as used to obtain benefits, including federal benefits